2017
DOI: 10.4174/astr.2017.93.3.152
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal membrane oxygenation support for refractory septic shock in liver transplantation recipients

Abstract: PurposeThis study was designed to assess the outcome of the extracorporeal membrane oxygenation (ECMO) in liver transplantation (LT) recipients with refractory septic shock and predict the prognosis of those cases.MethodsFrom February 2005 to October 2012, ECMO was used in 8 cases of refractory septic shock. Laboratory values including lactate and total bilirubin level just before starting ECMO were obtained and sepsis-related organ failure assessment (SOFA) score, acute physiology and chronic health evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 22 publications
(29 reference statements)
1
42
0
6
Order By: Relevance
“…A similar survival rate was reported when ECMO support was used as an acute resuscitation tool for in-hospital cardiac arrest [10,11]. On the other hand, Lee et al [1] reported that the survival rate of patients with refractory hypotension after liver transplantation who received ECMO was 25%. Enhanced survival after ECMO support was reported among patients who suffered from heart failure due to fulminant myocarditis and those who underwent VV-ECMO for H1N1-related ARDS.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…A similar survival rate was reported when ECMO support was used as an acute resuscitation tool for in-hospital cardiac arrest [10,11]. On the other hand, Lee et al [1] reported that the survival rate of patients with refractory hypotension after liver transplantation who received ECMO was 25%. Enhanced survival after ECMO support was reported among patients who suffered from heart failure due to fulminant myocarditis and those who underwent VV-ECMO for H1N1-related ARDS.…”
Section: Discussionsupporting
confidence: 61%
“…The benefits of the use of ECMO in various critical contexts, including cardiogenic shock, refractory septic shock, in-hospital cardiac arrest, ARDS or transplantation, have been reported in other series [1]. Among patients with cardiogenic shock or postcardiotomy syndrome who were receiving ECMO, the reported rate of survival to hospital discharge was between 24% and 45% [3,12,14].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Several publications [24][25][26][27] report on the use of ECMO in immunocompromised patients, mainly kidney and liver transplanted patients. Infections are the leading cause of critical illness and mortality in liver transplant patients.…”
Section: The Immunocompromised Patientmentioning
confidence: 99%
“…Mortality is higher in recipients with bacteremia due to 'ESKAPE' pathogens, which stands for Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa and Enterobacter species [28]. Over a 7-year period, a South Korean university center [24] used ECMO in 8 (of in total 854) liver transplanted patients with refractory septic shock. Primary liver disease in these patients was hepatocellular carcinoma (n = 3), liver cirrhosis due to hepatitis B infection (n = 3), alcoholic liver cirrhosis (n = 1) and toxic hepatitis (n = 1).…”
Section: The Immunocompromised Patientmentioning
confidence: 99%